STUDY OF PREPARATION AND CHARACTERIZATION OF HYDROXYAPATITE COATINGS BY SOL-GEL TECHNIQUE - Sutapa Roy Ramanan; Ramanan Venkatesh (ASEAN Journal on Science and Technology for Development, 2002)
Hydroxyapåtite (HAP) coatings were prepared on glass substrates by sol-gel dip coating method, using a isopropanol solution of calcium nitrate and 2-butanol solution of phosphorous pentoxide as starting precursors and mixing them to get a coating solution with Ca/P ratio of 1.67. The prepared coatings were dried at 150°C and subsequently  fired at 500°C to obtain dense coatings. Multilayer coatings were prepared to increase the final thickness. For some samples, SiO2, TiO2, Al2O, and Zr02 coatings modified the interface between the glass and HAP. X-ray diffraction, scanning electron microscopy, FTIR and DTA/TG were used for characterization. All the coatings obtained at 500°C in air had only crystalline hydroxyapatite phase, characteristics FTIR signature peaks of HAP and dense and smooth morphology with the apparent presence of micropores. The cross-sectional microstructure of the coatings showed presence of smooth interface.